Mixed‐Methods Study Identifying Key Intervention Targets to Improve Participation in Daily Living Activities in Primary Sjögren's Syndrome Patients. Issue 7 (21st May 2018) - Hackett, Katie L.; Deane, Katherine H. O.; Newton, Julia L.; Deary, Vincent; Bowman, Simon J.; Rapley, Tim; Ng, Wan‐Fai; ,
Abstract : Objective: Functional ability and participation in life situations are compromised in many primary Sjögren's syndrome (SS) patients. This study aimed to identify the key barriers and priorities to participation in daily living activities, in order to develop potential future interventions. Methods: Group concept mapping, a semiquantitative, mixed‐methods approach was used to identify and structure ideas from UK primary SS patients, adult household members living with a primary SS patient, and health care professionals. Brainstorming generated ideas, which were summarized into a final set of statements. Participants individually arranged these statements into themes and rated each statement for importance. Multidimensional scaling and hierarchical cluster analysis were applied to sorted and rated data to produce visual representations of the ideas (concept maps), enabling identification of agreed priority areas for interventions. Results: A total of 121 patients, 43 adult household members, and 67 health care professionals took part. In sum, 463 ideas were distilled down to 94 statements. These statements were grouped into 7 clusters: Patient Empowerment, Symptoms, Wellbeing, Access and Coordination of Health Care, Knowledge and Support, Public Awareness and Support, and Friends and Family. Patient Empowerment and Symptoms were rated as priority conceptual themes. Important statements within priority clusters indicate patients should be taken seriously and supported to self‐manage symptoms of oral and ocular dryness, fatigue, pain, and poor sleep. Conclusion: Our data highlighted the fact that in addition to managing primary SS symptoms, interventions aiming to improve patient empowerment, general wellbeing, access to health care, patient education, and social support are important to facilitate improved participation in daily living activities.